The Popular and the Academic: The Status of the Public’s Pleasure in the Quarrel of Le Cid. - Kristinsdóttir-Urfalino, Guðrún (Nordic Theatre Studies, 2018)
The unprecedented success of Le Cid (1637) triggered a ferocious literary quarrel about the value of the judgement of the least “considerable” part of the theatre audience – the people. This article explains how the social and gendered distribution of the audience in the few Parisian theatres of the period could reveal the difference of the appreciation of various categories of the audience. The article then develops that at this time in France, the notion of the “public” does not refer to the audience but to the res publica, the edifying character of the plays meant to serve the public good. Indeed, the theatre was given a moral dimension, as an heritage to Horace’s Ars poetica in which the role of theatre was to please and instruct. This is followed by a discussion of two aspects of the quarrel. It was first set off by the fact that Corneille with his attitude disrupted the rules of the economy of cooptation in vigour in the Republic of letters, thus deeply shocking his peers. The second aspect of the quarrel pertained to the dramatic rules which were being established at the time. Le Cid transgressed some of these rules, in particular the rule of decorum. But the condemnation of the transgression of these rules put in question their purpose and their value. Corneille maintained that like Aristotle, he was concerned with the public’s pleasure and that Horace’s precept of moral instruction was secondary in theatre. The conjunction of the criticism of peers concerning the non-respect of the dramatic rules and the actual success with the public posed the question of the valid tribunal of literary works – peers or the public. Ultimately, the fact that the play had touched all categories of the audience – the people and the courtiers – facilitated the valorization of the people’s pleasure and the people’s judgement vis-à-vis the peers.